Pengaruh waktu induksi dan ZPT terhadap pertumbuhan kalus kotiledon kacang panjang (Vigna unguiculata subsp. sesquipedalis) - Kuswandi, Paramita Cahyaningrum; Husna, Selma Nafilatul (Jurnal Biologi Udayana; Vol 27 No 2 (2023): JURNAL BIOLOGI UDAYANA, 2023)
Yard-Long bean plants are an agricultural commodity that has great potential to be developed because they are easy to cultivate, their market share is also quite high but there are still problems in meeting the need for sufficient seeds and they are still susceptible to pests and disease. Therefore, efforts need to be made to increase production and induce variations. One method that can be used is tissue culture for the induction of somaclonal variations and/or the formation of transgenic plants. This study aims to determine the effect of variations in callus initiation time and the effect of Plant Growth Regulators (PGR) administration on the growth of long bean cotyledon explant callus. Seed sterilization was carried out using detergent, 10% sodium hypochlorite, 70% alcohol and sterile distilled water. The results of the research showed that variations in callus initiation time on MS media with the addition of 2,4-D PGR and the use of several variations of PGR in subcultures were able to initiate callus and influence callus size, callus color, and the percentage of browning of Yard-long bean cotyledon explants. Callus initiation time of 4 weeks with a combination of 2 ppm BAP concentration with 0.1 ppm IAA produced the largest callus size and brownish white callus color. The addition of PGR during subculture had a smaller browning percentage than the treatment without PGR.